Fondos aragoneses en la fototeca del CSIC - Rincón García, Wifredo; Villalón Herrera , Rosa M.ª; Ibáñez González , Raquel (Artigrama, 2012)
ResumenLa antigua «Fototeca» del Instituto de Historia del Arte «Diego Velázquez», hoy Archivo Fotográfico del Centro de Ciencias Humanas y Sociales del CSIC, conserva entre sus fondos una importante serie de fotografías que reproducen obras de arte existentes en el territorio aragonés, así como otras muchas realizadas por artistas aragoneses y conservadas en distintos lugares.AbstractThe ancient Photographic Archive of the History of Art “Diego Velázquez”, nowadays Photographic Archive of CCHS, keeps among its collections an important number of images that reproduces works of art belonging to Aragón and many others which were done by artists from Aragón and kept in different places.Key wordsAragón, photography, Photographic Archive of CCHS, art, architecture, sculpture, pain-ting, decorative arts.